Techne theory : a new language for art - Staten, Henry, 1946- (Bloomsbury Academic, 2019)
"Only since the Romantic period has art been understood in terms of an ineffable aesthetic quality of things like poems, paintings, and sculptures, and the art-maker as endowed with an inexplicable power of creation. From the Greeks to the 18th century, art was conceived as techne--the skill and know-how by which things and states of affairs are ordered. Techne Theory shows how to use this concept to cut through the Romantic notion of art as a kind of magic by returning to the original sense of art as techne, the standpoint of the person who actually knows how to make a work of art. Understood as techne, art-making, like all other cultural accomplishments, is a form of work performed by an artisan who has inherited the know-how of previous generations of artisans. Along the way, Techne Theory cuts through the humanist-structuralist impasse over the question of artistic agency and explains what 'form' really means."--Bloomsbury Publishing